Pengaruh Struktur Ekonomi Daerah dan Investasi Asing terhadap Pertumbuhan Inklusif di Indonesia - Puja Kurnia; Selli Nelonda (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Since the 1998 monetary crisis, Indonesia's economy has grown positively, but its distribution is still uneven, especially for low-income groups. This study analyzes the influence of regional economic structure and foreign investment on inclusive growth in Indonesia for the 2019–2023 period using panel data from 34 provinces and the Fixed Effect Model (FEM) method. The results show that the trade, Foreign Investment (FDI), and education sectors have a significant positive effect, while the services sector has a negative effect on inclusive growth. The agriculture, mining, industry, and ICT skills sectors have no significant effect. These findings underscore the importance of strengthening trade, education, and the optimization of foreign investment to drive more equitable growth.